Ex vivo cytokine production in psoriatic disease: Towards specific signatures in cutaneous psoriasis and peripheral psoriatic arthritis - Larid, Guillaume; Delwail, Adriana; Dalle, Thomas; Vasseur, Philippe; Silvain, Christine; Jégou, Jean-François; Morel, Franck; Lecron, Jean-Claude; Gervais, Elisabeth (Frontiers in Immunology, 2022)
Objectives: Psoriatic arthritis (PsA) and cutaneous psoriasis (PsO) are different phenotypes of psoriatic disease (PsD), whose underlying specific mechanisms remain incompletely understood. As cytokines are key elements to induce and tune up immune responses to drive inflammatory diseases, our objective was to assess whether clinical features, disease phenotype and PsA and PsO activity were associated with a particular ex vivo cytokine production profile. Methods: Forty-eight patients (37 PsA and 11 PsO) and 11 healthy subjects (HS) were studied. Cytokine production by peripheral blood mononuclear cells (PBMC) that were either unstimulated, or stimulated with LPS or anti-CD3/CD28 antibodies, were analysed by multiplex assay in the culture supernatants. Results: Cytokine signature of PsD includes a high level of TNFα in supernatants of LPS-stimulated PBMC, higher levels of IL-6 and lower levels of IFN-γ and IL-17A after CD3-CD28 stimulation, as well as higher spontaneous IL-1RA and TNFα production compared to HS. High body mass index (BMI) was associated with lower levels of IL-1β, and metabolic syndrome with lower levels of IFN-γ after LPS stimulation. In PsD, dermatological activity was related with higher IL-17A level, while rheumatic activity was linked with lower levels of IFN-γ and TNFα. Comparing each PsD subtype to HS, IL-1β and IL-6 productions are higher when using LPS stimulation in PsO patients with higher levels of IL-1β and IL-1α in peripheral PsA patients after CD3/CD28 stimulation. LPS stimulation induced high levels of IL-17A in peripheral PsA compared to axial PsA. PsA patients with axial PsA share some features with PsO but shows a distinct cytokine pattern compared to peripheral PsA. Conclusion: PsO and the different PsA subtypes exhibit distinct ex vivo cytokine production profiles and common features of the so-called PsD. Analysis of IL-1 cytokine family and IL-6 seems to be of particular interest to distinguish PsO and peripheral PsA since it depends on monocytes in PsO and T-lymphocytes in peripheral PsA. Peripheral cytokine profiles are influenced by rheumatic and dermatological activity of the disease, and also by metabolic syndrome features. Our results highlight the crucial role of immune cell interactions with different patterns of interaction depending on clinical phenotype.